Use of 3He Neutron Sensors for Planetary Penetrator Experiments - David J. Lawrence; Bruce L. Barraclough; Richard C. Elphic; Paul G. Lucey (Earth and Space Science)
Abstract This paper provides a report on a test that was carried out over 20 years ago to demonstrate that two 3He gas proportional neutron sensors could survive a high‐impact penetrator test. This test was carried out as part of a risk reduction effort for a proposed mission that would send multiple penetrators to landing locations within lunar permanently shaded regions (PSRs). After landing, the neutron sensors would carry out in situ measurements within the PSRs to quantify the hydrogen abundances within these regions. Two penetrator shots were successfully carried out with the neutron sensors enclosed in the penetrators. The deceleration value for the shots exceeded 1,400 G's over less than 20 milliseconds. Pre‐ and post‐penetration measurements of the 3He sensors show that the sensors themselves suffered no degradation in performance; one non‐spaceflight quality high‐voltage connector did indicate performance degradation. These results provide confidence that these types of 3He neutron sensors could be successfully used in a future penetrator mission to a planetary body.